Answer:
[tex]\large\boxed{x-intercept=-2+\sqrt[3]{0.01}}[/tex]
Step-by-step explanation:
[tex]f(x)=3\log(x+5)+2\to y=3\log(x+5)+2\\\\\text{Domain:}\ x+5>0\to x>-5\\\\\text{x-intercept is for }\ y=0:\\\\3\log(x+5)+2=0\qquad\text{subtract 2 from both sides}\\\\3\log(x+5)=-2\qquad\text{divide both sides by 3}\\\\\log(x+5)=-\dfrac{2}{3}\qquad\text{use the de}\text{finition of logarithm}\\\\(\log_ab=c\iff b^c=a),\ \log x=\log_{10}x\\\\\log(x+2)=-\dfrac{2}{3}\\\\\log_{10}(x+2)=-\dfrac{2}{3}\iff x+2=10^{-\frac{2}{3}}\qquad\text{use}\ a^{-n}=\left(\dfrac{1}{a}\right)^n[/tex]
[tex]x+2=\left(\dfrac{1}{10}\right)^\frac{2}{3}\qquad\text{use}\ \sqrt[n]{a^m}=a^\frac{m}{n}\\\\x+2=\sqrt[3]{0.1^2}\qquad\text{subtract 2 from both sides}\\\\x=-2+\sqrt[3]{0.01}\in D[/tex]
What is the sum of sqrt -2 and sqrt -18
Answer:
4i sqrt(2)
Step-by-step explanation:
sqrt(-2) + sqrt(-18)
We know sqrt(ab)= sqrt(a) sqrt(b)
sqrt(-1)sqrt(2) + sqrt(9) sqrt(-2)
sqrt(-1)sqrt(2) + sqrt(9) sqrt(2)sqrt(1)
We know the sqrt(-1) is equal to i
i sqrt(2) +3 sqrt(2) i
i sqrt(2) +3i sqrt(2)
4i sqrt(2)
simplify the trigonometric expression tan(2x)/tan(x) using double-angle identities !!
A. 2/1-tan^2(x)
B. 2tan(x)/1-tan^2(x)
C. 2tan(x)/1-tan^3(x)
D. tan(x)
The correct solution is,
⇒ 2 / (1 - tan²x)
What is an expression?Mathematical expression is defined as the collection of the numbers variables and functions by using operations like addition, subtraction, multiplication, and division.
Given that;
The expression is,
⇒ tan (2x) / tan x
Now, We know that;
tan 2x = (2 tanx / 1 - tan²x)
Hence, We can simplify as;
⇒ tan (2x) / tan x
⇒ (2tan (x) /1 - tan²x) / tan x
⇒ 2 / (1 - tan²x)
Thus, The correct solution is,
⇒ 2 / (1 - tan²x)
Learn more about the mathematical expression visit:
brainly.com/question/1859113
#SPJ2
The expression tan(2x)/tan(x) simplifies using the double-angle identity for tangent to 2/(1 - tan^2(x)), which corresponds to Option A.
To simplify the trigonometric expression tan(2x)/tan(x) using double-angle identities, we can use the double-angle identity for tangent:
tan(2x) = 2tan(x)/(1 - tan2(x)).
Now, if we divide tan(2x) by tan(x), we get:
tan(2x)/tan(x) = (2tan(x)/(1 - tan2(x)/tan(x).
With tan(x) in the numerator and denominator, it cancels out, leaving:
2/(1 - tan2(x)).
Therefore, the correct answer is Option A: 2/(1 - tan2(x)).
A particular model of walkie-talkie can broadcast in a circular area. The radius of the broadcast area is 7,000 feet. Find the area of this circle to the nearest square foot. Use 3.14 for π.
Answer:
153938040.0259 ft2
Step-by-step explanation:
R= Square root of A/π
Answer:
153,860,000 ft^2.
Step-by-step explanation:
The area = 3.14 * r^2
= π * 7,000^2
= 153,860,000 ft^2.
What is the value of the product (3-21) (3 + 21)?
The value of the product (3 - 21) * (3 + 21) is -432, obtained by applying the distributive property.
To find the value of the product (3 - 21) * (3 + 21), we can use the distributive property or the difference of squares identity. Here's how it works:
(3 - 21) * (3 + 21) = (3 - 21) * [(3) + (21)] (Apply the distributive property)
Now, let's calculate each part:
1. (3 - 21) = -18
2. (3 + 21) = 24
Now, we multiply these results together:
-18 * 24 = -432
So, the value of the product (3 - 21) * (3 + 21) is -432.
For such more questions on product
https://brainly.com/question/1712056
#SPJ2
Final answer:
The product of (3-21) and (3 + 21) is -324.
Explanation:
The value of the product (3-21) (3 + 21) is -324.
To find the product, first calculate the values within the parentheses:
3 - 21 = -18
3 + 21 = 24
Multiply these two values: -18 * 24 = -324.
solve for the indicated variable
ax+r=7, for x
Answer:
x = [tex]\frac{7 - r}{a}[/tex]
Step-by-step explanation:
ax+r=7
ax = 7 - r
x = [tex]\frac{7 - r}{a}[/tex]
What is the value of X?
Answer:
x ≈ 6.6 cmStep-by-step explanation:
It's a right triangle.
Use the Pythagorean theorem:
[tex]leg^2+leg^2=hypoyenuse^2[/tex]
We have:
[tex]leg=13.5\ cm,\ leg=x\ cm,\ hypotenuse=(x+8.45)\ cm[/tex]
Substitute:
[tex]13.5^2+x^2=(x+8.45)^2\qquad\text{use}\ (a+b)^2=a^2+2ab+b^2\\\\182.25+x^2=x^2+2(x)(8.45)+8.45^2\qquad\text{subtract}\ x^2\ \text{from both sides}\\\\182.25=16.9x+71.4025\qquad\text{subtract 71.4025 from both sides}\\\\110.8475=16.9x\qquad\text{divide both sides by 16.9}\\\\\dfrac{110.8475}{16.9}=x\to x\approx6.6\ cm[/tex]
Solve by using the quadratic formula.
3psquared+7p+2=0
Answer:
[tex]\large\boxed{x=-2\ or\ x=-\dfrac{1}{3}}[/tex]
Step-by-step explanation:
The quadratic formula of a quadratic equation
[tex]ax^2+bx+c=0\\\\x=\dfrac{-b\pm\sqrt{b^2-4ac}}{2a}[/tex]
We have the equation:
[tex]3p^2+7p+2=0\to a=3,\ b=7,\ c=2[/tex]
Substitute:
[tex]b^2-4ac=7^2-4(3)(2)=49-24=25\\\\\sqrt{b^2-4ac}=\sqrt{25}=5\\\\x_1=\dfrac{-7-5}{2(3)}=\dfrac{-12}{6}=-2\\\\x_2=\dfrac{-7+5}{2(3)}=\dfrac{-2}{6}=-\dfrac{1}{3}[/tex]
Answer:
-1/3,-2
Step-by-step explanation:
The quadratic formula is [-b±√(b^2-4ac)]/2a. In this equations 3p^2 is a, 7p is b, and 2 is c.
Then just plug in the numbers.
[-7±√((-7^2)-4(3)(2)]/2(3)
[-7±√(25)]/6
(-7+5)/6 and (-7-5)/6
-1/3 and -2 are the answers, if you plug these numbers into the original equation, you find that they equal 0 which means that they work.
How do the solutions to an equation relate to the graph of the equation?
How do you solve a system of equations approximately using graphs and tables?
need it in 2 paragraph I will 100% leave thanks and 5 star
Answer:
Ok
Step-by-step explanation: what is this???????
A square pyramid has the sides of the base of 4 cm and a height of 10 cm, what is its surface area?
Answer:
A = 44.2cm²
Step-by-step explanation:
The surface area of a square pyramid that has the sides of the base of 4 cm and a height of 10 cm is 44.2cm².
Formula: A=AB(4h2+AB)+AB
A=AB(4h2+AB)+AB=4·(4·102+4)+4≈44.1995cm²
What mistake did the student make?
Answer:
A
Step-by-step explanation:
if he had multiplied the 2nd equation by 9 throughout successfully, he would have gotten :
6x - y = 16 (multiply by 9)
54x - 9y = 144
Answer:
(a) The error is in step 1.
See below.
Step-by-step explanation:
They did not multiply the 16 by 9.
SOLVE 4x + 3y = –5 -2x + 2y = 6 BY USING ELIMINATION. SHOW ALL WORK!!! HELPPPP :)))) THANKS! ;)
Answer:
x= [tex]\frac{-1}{6}y+\frac{-11}{6}[/tex]
y=6x+11
Step-by-step explanation:
4x + 3y = –5 -2x + 2y = 6
- 4x - 3y –5 -2x + 2y = 6
- 4x - 3y -2x + 2y = 6+5
-4x - 3y -2x +2y =11
-6x-y= 11
Given the lengths of the sides, state if the triangle is acute, obtuse, or right. 8, 15, and 17 This is a(n) blank triangle.
Answer:
This is a right triangle
Step-by-step explanation:
Pythagoras theorem is used to determine if a triangle is right, acute or obtuse
If the sum of squares of two shorter lengths is greater than the square of third side then the triangle is an acute triangle.
If the sum of squares of two shorter lengths is less than the square of third side then the triangle is an obtuse triangle.
If the sum of squares of two shorter lengths is equal the square of third side then the triangle is a right triangle.
so,
[tex](17)^2 = (15)^2+(8)^2\\289 = 225+64\\289=289[/tex]
Therefore, the given triangle is a right triangle ..
Un muchacho compra el mismo numero de lapices que de lapiceros por 90 soles.Cada laliz le cuesta 3 soles y cada lapicero 7 soles. ¿Cuantos lapices y lapiceros ha comprado?
The boy bought 9 pencils and 9 pens, with a total cost of 90 soles. This calculation is based on the cost of 3 soles per pencil and 7 soles per pen, resulting in a total expenditure that aligns with the given information.
1: Define the costs.
We know the cost of each pencil and pen:
Pencils: 3 soles each
Pens: 7 soles each
2: Let x be the number of items.
Since the boy buys the same number of pencils and pens, let x represent the number of each item he buys.
3: Set up the total cost equation.
The total cost he spends is 90 soles. We can express this as an equation:
Total cost = Pencils cost + Pens cost
90 soles = (x pencils * 3 soles/pencil) + (x pens * 7 soles/pen)
4: Simplify and solve for x.
Combine like terms:
90 soles = 3x soles + 7x soles
90 soles = 10x soles
x = 90 soles / 10 soles/item
x = 9 items
5: Find the number of pencils and pens.
Since x represents both the number of pencils and pens, he bought 9 pencils and 9 pens.
Therefore, the boy bought 9 pencils and 9 pens.
Complete question:
A boy buys the same number of pencils as pencils for 90 soles. Each pencil costs 3 soles and each pencil 7 soles. How many pencils and pens has he bought?
Consider this equation.
7.8 + 2(0.75m + 0.4) = -6.4m + 4(0.5m - 0.8)
Mia solved the equation and determined that m = 2. Is she correct?
A. She is incorrect because when substituting 2 for m the result was a true statement.
B. She is incorrect because when substituting 2 for m the result was a false statement.
C. She is correct because when substituting 2 for m the result was a true statement.
D. She is correct because when substituting 2 for m the result was a false statement.
Answer:
B if m=2
(Just to make sure that isn't m=-2, right?)
Step-by-step explanation:
7.8 + 2(0.75m + 0.4) = -6.4m + 4(0.5m - 0.8)
Let's plug in 2 for m.
7.8+2(0.75*2+0.4) = -6.4*2+4(0.5*2-0.8)
If 2 is a solution, then both sides will be the same.
If 2 is not a solution, then both sides will be different.
If both sides are the same, it is a true equation.
If both sides are different, it is a false equation.
Let's simplify 7.8+2(0.75*2+0.4)
According to PEMDAS, we must perform the operations in the parenthesis.
We have multiplication and addition in ( ). We will do the multiplication because the MD comes before the AS.
0.75*2=1.5
So now our expression 7.8+2(0.75*2+0.4) becomes 7.8+2(1.5+0.4)
Now to do the addition in the ( ).
1.5+0.4=1.9.
So now our expression 7.8+2(0.75*2+0.4) becomes 7.8+2(1.9).
We have multiplication to be perform now because again MD becomes before AS.
7.8+2(0.75*2+0.4) becomes 7.8+3.8
Last step perform the addition (the only operation left here on the left hand side)
7.8+2(0.75*2+0.4) becomes 11.6 .
Let's focus on the right now.
-6.4*2+4(0.5*2-0.8)
-6.4*2+4(1 -0.8) I did the multiplication in the ( ) first.
-6.4*2+4(.2) I did the subtracting in the ( ).
-12.8+.8 I did the multiplication by -6.4*2 and 4*.2 simultaneously
-12
I'm going to put all of this together because I think it might be easier to read:
7.8 + 2(0.75m + 0.4) = -6.4m + 4(0.5m - 0.8)
Plug in 2 for m
7.8 + 2(0.75*2 + 0.4)=-6.4*2 + 4(0.5*2 - 0.8)
7.8 + 2(1.5 + 0.4)= -6.4*2 + 4(1 -0.8)
7.8 + 2(1.9) = -6.4*2 + 4(.2)
7.8 + 3.8 = -12.8 +.8
11.6 =-12
This is false because 11.6 is not the same as -12.
m=2 leads to a false equation
B.
The value of m for the expression 7.8 + 2(0.75m + 0.4) = -6.4m + 4(0.5m - 0.8) is -2. Hence, Mia's statement is false.
What is Simplification?Simplification in mathematical terms is a process to convert a long mathematical expression in simple and easy form.
The given equation is,
7.8 + 2(0.75m + 0.4) = -6.4m + 4(0.5m - 0.8)
Also, Mia solved the equation and determine that the value of m is 2.
To find the value of m, simplify the expression,
7.8 + 1.5m + 0.8 = -6.4m + 2m - 3.2
1.5m + 8.6 = -4.4m - 3.2
1.5m + 4.4m = -3.2 - 8.6
5.9m = -11.8
m = -2
Mia is incorrect because the value of m is -2,
Therefore the statement is false.
To know more about Simplification on :
https://brainly.com/question/2804192
#SPJ3
Jill has quiz scores of 74, 72, 76, 80, and 73. To continue to receive her scholarship, Jill must maintain an average of 75. What is the lowest grade Jill needs to have on the next quiz to keep her scholarship?
A. 77
B. 75
C. 73
D. 71
Answer:
B
Step-by-step explanation:
(74+72+76+80+73+(AnswerB)75)÷6(total number of quizzes include the one she needed to take)=75(minimum average because she needs to get average of 75)
Is the equation below a sum of cubes
125x3 +169
Answer:
NOStep-by-step explanation:
[tex]\text{Because}\\\\125x^3=5^3x^3=(5x)^3\qquad\bold{it's\ a\ cube}\\\\169=13^2\qquad\bold{it's \ a \ square}\\\\125x^3+169=(5x)^3+13^2[/tex]
[tex]13-\text{it's a prime number}[/tex]
A right cylinder has a radius of 2 units and a height of 5
units.
What is the volume of the cylinder? Round to the nearest
tenth.
31.4 cubic units.
62.8 cubic units
157.1 cubic units
314.2 cubic units.
Answer:
62.8
Step-by-step explanation:
The volume of the cylinder is = base * height
base=Pi*radius*radius, where
base=3.1416*2*2 , height=5
Volume=3.1416*2*2*5
Volume =62.8 cubic units.
Answer:
Option B.
Step-by-step explanation:
It is given that right cylinder has a radius of 2 units and a height of 5 units. It means
r = 2
h = 5
The volume of a right cylinder is
[tex]V=\pi r^2h[/tex]
where, r is radius and h is height of the cylinder.
Substitute r=2 and h=5 in the above formula.
[tex]V=\pi (2)^2(5)[/tex]
[tex]V=\pi (4)(5)[/tex]
[tex]V=20\pi[/tex]
On further simplification we get
[tex]V=62.831853[/tex]
[tex]V\approx 62.8[/tex]
The volume of right cylinder is 62.8 cubic units.
Therefore, the correct option is B.
What is the equation of the oblique asymptote?
h(x)= x^2-3x-4/x+1
___________________________________________
○A. y=x+4
○B. y= x
○C. y= x^2-3
○D. y=x-4
Answer:
y=x-4
Step-by-step explanation:
What you are looking for is also known as the slant asymptote. The slant asymptote occurs when the degree of the numerator is one degree more than the denominator which is what you have.
So to find the slant asymptote we can use polynomial division.
We have a choice to use synthetic division here because the denominator is linear.
-1 goes on the outside because we are dividing by (x+1).
-1 | 1 -3 -4
| -1 4
|----------------------
1 -4 0
The asymptote is the quotient part which is y=x-4.
So answer is y=x-4.
Option D is correct, y=x-4 is the equation of the oblique asymptote h(x)= x²-3x-4/x+1
What is Equation?Two or more expressions with an Equal sign is called as Equation.
To find the equation of the oblique asymptote, we need to perform polynomial division of the numerator (x² - 3x - 4) by the denominator (x + 1):
x - 4
------------
x + 1 | x² - 3x - 4
x² + x
-------
-4x - 4
-4x - 4
-------
0
The quotient is x - 4, which represents the equation of the slant asymptote.
Hence, y=x-4 is the equation of the oblique asymptote h(x)= x²-3x-4/x+1
To learn more on Equation:
https://brainly.com/question/10413253
#SPJ7
The overhead reach distances of adult females are normally distributed with a mean of 205 cm205 cm and a standard deviation of 8.6 cm8.6 cm.
a. Find the probability that an individual distance is greater than 215.00215.00 cm.
b. Find the probability that the mean for 2525 randomly selected distances is greater than 203.70 cm.203.70 cm.
c. Why can the normal distribution be used in part (b), even though the sample size does not exceed 30?
Answer:
a) P(z>1.16) = 0.8770
b) P(z>-0.75) = 0.2266
Step-by-step explanation:
Mean = 205 cm
Standard Deviation = 8.6 cm
a) Find the probability that an individual distance is greater than 215.00
We need to find P(X>215)
x = 215
z = x - mean /standard deviation
z = 215 - 205 / 8.6
z = 1.16
P(X>215)=P(z>1.16)
Finding value of z =1.16 from the table
P(z>1.16) = 0.8770
b) Find the probability that the mean for 25 randomly selected distances is greater than 203.70 cm
Sample size n= 25
x = 203.70
mean = x- mean / standard deviation / √sample size
mean = 203.70 - 205 / 8.6 / √25
mean = -1.3/8.6/5
mean = -0.75
Finding value from z-score table
P(mean >-0.75) = 0.2266
c) Why can the normal distribution be used in part (b), even though the sample size does not exceed 30?
If the original problem is normally distributed, then for any sample size n, the sample means are normally distributed.
What would the next figure in the geometric pattern below be?
Answer:
Hi there!
The answer to this question is: D
Step-by-step explanation:
The pattern is; up (red), down (blue), up (red)
so therefore the next pattern is down (blue) which is D
To find the next figure in the geometric pattern, analyze the given information and identify the pattern in the dot placements. Based on the description, each figure is obtained by adding dots in specific positions. The next figure can be determined by continuing this pattern.
Explanation:The next figure in the geometric pattern can be determined by analyzing the given information. Based on the description, we can infer that each figure is obtained by adding dots in a specific pattern. The third dot is located one and two-thirds perpendicular hash marks to the right of the center top perpendicular hash mark, while the fourth dot is in the same position as the Car X figure (one perpendicular hash mark above the center right perpendicular hash mark). To find the next figure, we need to continue this pattern by adding dots in the specified positions.
what is the sum of the first four terms of a geometric series with 2 as its first term and a common ratio of 1/3
[tex]\bf \qquad \qquad \textit{sum of a finite geometric sequence} \\\\ \displaystyle S_n=\sum\limits_{i=1}^{n}\ a_1\cdot r^{i-1}\implies S_n=a_1\left( \cfrac{1-r^n}{1-r} \right)\quad \begin{cases} n=\textit{last term's}\\ \qquad position\\ a_1=\textit{first term}\\ r=\textit{common ratio}\\ \cline{1-1} n=4\\ a_1=2\\ r=\frac{1}{3} \end{cases}[/tex]
[tex]\bf S_4=2\left( \cfrac{1-\left( \frac{1}{3} \right)^4}{1-\frac{1}{3}} \right)\implies S_4 = 2\left( \cfrac{1-\frac{1}{81}}{\frac{2}{3}} \right)\implies S_4 = 2\left( \cfrac{\frac{80}{81}}{~~\frac{2}{3}~~} \right) \\\\\\ S_4=2\left( \cfrac{40}{27} \right)\implies S_4=\cfrac{80}{27}\implies S_4=2\frac{26}{27}[/tex]
Answer:
80/27.
Step-by-step explanation:
Sum of n terms = a1 * (1 - r^n) / (1 - r)
Sum of 4 terms = 2 * (1 -(1/3)^4) / ( 1 - 1/3)
= 2 * 80/81 / 2/3
= 160 / 81 * 3/2
= 480/ 162
= 80/27 (answer
Which statement proves that △XYZ is an isosceles right triangle? XZ ⊥ XY XZ = XY = 5 The slope of XZ is , the slope of XY is , and XZ = XY = 5. The slope of XZ is , the slope of XY is , and the slope of ZY = 7.
Answer:
The slope of XZ is 3/4 , the slope of XY is -4/3 , and XZ = XY = 5 ⇒ 3rd answer
Step-by-step explanation:
* Lets look to the attached figure to solve the problem
- To prove that the Δ XYZ is an isosceles right triangle, you must
find two sides the product of their slopes is -1 and they are equal
in lengths
- From the figure the vertices of the triangle are;
X = (1 , 3) , Y = (4 , -1) , Z = (5 , 6)
- The slope of the line whose endpoints are (x1 , y1) and (x2 , y2)
is [tex]m=\frac{y_{2}-y_{1}}{x_{2}-x_{1}}[/tex]
∵ The slope of [tex]XY=\frac{-1-3}{4-1}=\frac{-4}{3}[/tex]
∵ The slope of [tex]XZ=\frac{6-3}{5-1}=\frac{3}{4}[/tex]
∴ The slope of XY = -4/3 , the slope of XZ = 3/4
∵ -4/3 × 3/4 = -1
∴ XY ⊥ XZ
∴ ∠ X is a right angle
∴ Δ XYZ is a right triangle
- The distance between the two points (x1 , y1) and (x2 , y2) is
[tex]d=\sqrt{(x_{2}-x_{1})^{2}+(y_{2}-y_{1})^{2}}[/tex]
∵ [tex]XY=\sqrt{(4-1)^{2}+(-1-3)^{2}}=\sqrt{9+16}=\sqrt{25}=5[/tex]
∵ [tex]XZ=\sqrt{(5-1)^{2}+(6-3)^{2}}=\sqrt{16+9}=\sqrt{25}=5[/tex]
∴ XY = XZ = 5
∴ Δ XYZ is an isosceles right triangle
* The statement which prove that is:
The slope of XZ is 3/4 , the slope of XY is -4/3 , and XZ = XY = 5
Answer:
its C
Step-by-step explanation:
yw :)
The blue segment below is a diameter of O. What is the the length of the radius of the circle?
Answer:
2.95
Step-by-step explanation:
The radius of a circle is half of the diameter.
r = (1/2)d
r = (1/2)(5.9)
r = 2.95
Answer:
radius = 2.95
Step-by-step explanation:
The radius is the distance from the centre O to the circumference and is one half the diameter,
radius = 0.5 × 5.9 = 2.95
[tex]x {}^{2} - x[/tex]
Factorizations by difference in two squares.
[tex]x^2-x[/tex] is nothing interesting you can just factor out x and result with [tex]x(x-1)[/tex].
However the difference of squares is defined as,
[tex]a^2-b^2=(a+b)(a-b)[/tex]
Hope this helps.
r3t40
What’s equivalent to 1/7-3(3/7n-2/7) combine like terms
Answer:
(1/7)(-9n + 7)
Step-by-step explanation:
1/7-3(3/7n-2/7) can be factored: factor out 1/7.
We get: (1/7)[1 - 3(3n - 2)], or
(1/7)[1 - 9n + 6], or
(1/7)(-9n + 7)
Martin runs 100 meters in 15 seconds. What is the equation for d, the distance in meters that Martin covers per second
Answer:
d = 6.67s
Step-by-step explanation:
This is the answer because if you take 100 and divide it by 15, then you get d as 6.6666, which rounds up to 6.67s.
7. A photograph negative measures 15 inches by
2- inches. The printed picture is to have its
longer dimension be 4 inches. How long should
the shorter dimension be?
(A) 2
(B) 3”
(C)35"
(D) 32»
Answer:
First we need to set a proportion
Currently the negative measures 15 inches by 2 inches. And the longer dimension of the printed version is 4 inches. Therefore:
[tex]\frac{2}{y} = \frac{15}{4}[/tex]
[tex]15y = 8[/tex]
[tex]y = 0.5333[/tex]
Therefore, the dimension of the shorter dimension is 0.5333.
None of the options matches this response, so maybe you forgot to add some information?
what is the simplest form of x2+5x+-6/ x2+9x+18
Answer:
[tex]\frac{x-1}{x+3}[/tex]
Step-by-step explanation:
Let's factor the numerator and denominator first.
x^2+5x-6 is a quadratic in the form of x^2+bx+c.
If you have a quadratic in the form of x^2+bx+c, all you have to do to factor is think of two numbers that multiply to be c and add to be b.
In this case multiplies to be -6 and adds to be 5.
Those numbers are 6 and -1 since -1(6)=-6 and -1+6=5.
So the factored form of x^2+5x-6 is (x-1)(x+6).
x^2+9x+18 is a quadratic in the form of x^2+bx+c as well.
So we need to find two numbers that multiply to be 18 and add to be 9.
These numbers are 6 and 3 since 6(3)=18 and 6+3=9.
So the factored form of x^2+9x+18 is (x+3)(x+6).
So we have that:
[tex]\frac{x^2+5x+-6}{x^2+9x+18}=\frac{(x-1)(x+6)}{(x+3)(x+6)}[/tex]
We can simplify this as long as x is not -6 as
[tex]\frac{x-1}{x+3}[/tex]
I obtained the last line there by canceling out the common factor on top and bottom.
Answer:
We can simplify this as long as x is not -6 as
\frac{x-1}{x+3}
Step-by-step explanation:
What else would need to be congruent to show that ABC = XYZ by ASA?
Answer:
Option B AC≅XZ
Step-by-step explanation:
we know that
ASA (angle, side, angle) means that we have two congruent triangles where we know two angles and the included side are equal
In this problem we have
∠X≅∠A
∠Z≅∠C
In the triangle ABC the included side between the angles ∠A and ∠C is the side AC
and
In the triangle XYZ the included side between the angles ∠X and ∠Z is the side XZ
therefore
AC≅XZ
Select the two values of x that are roots of this equation. x^2+2x-4=0
Answer:
[tex]\large\boxed{x=-1\pm\sqrt5}[/tex]
Step-by-step explanation:
[tex]x^2+2x-4=0\qquad\text{add 4 to both sides}\\\\x^2+2x=4\\\\x^2+2(x)(1)=4\qquad\text{add}\ 1^2=1\ \text{to both sides}\\\\\underbrace{x^2+2(x)(1)+1^2}=4+1^2\qquad\text{use}\ (a+b)^2=a^2+2ab+b^2\\\\(x+1)^2=5\to x+1=\pm\sqrt5\qquad\text{subtract 1 from both sides}\\\\x=-1\pm\sqrt5[/tex]
The two values of x for the given equation are ( -1 + √5 ) and ( - 1 - √5 ).
What is a quadratic equation?The polynomial having a degree of two or the maximum power of the variable in a polynomial will be 2 is defined as the quadratic equation and it will cut two intercepts on the graph at the x-axis.
The solution of the given equation is:-
= x² + 2x - 4
x² + 2x = 4
x² + 2x ( 1 ) + 1² = 4 + 1²
( x + 1 )² = 5
x + 1 = ± √5
x = -1 ± √5
Therefore the two values of x for the given equation are ( -1 + √5 ) and ( - 1 - √5 ).
To know more about quadratic equations follow
https://brainly.com/question/1214333
#SPJ2